Essentials of cloud application development on IBM Bluemix : presentations guide - Aziz, Hala A. (IBM redbooks., 2016)
Abstract This IBM® Redbooks® publication is based on the Presentations Guide of the course "Essentials of Cloud Application Development on IBM Bluemix" that was developed by the IBM Redbooks team in partnership with IBM Middle East and Africa (MEA) University Program. This course is designed to teach university students the basic skills that are required to develop, deploy, and test cloud-based applications that use the IBM Bluemix® cloud services. The primary target audience for this course is university students in undergraduate computer science and computer engineer programs with no previous experience working in cloud environments. However, anyone new to cloud computing can benefit from this course. After completing this course, you should be able to accomplish these tasks: Describe the factors that lead to the adoption of cloud computing. Describe infrastructure as a service, platform as a service, and software as a service. Define cloud computing. Describe IBM Bluemix. Describe the architecture of IBM Bluemix. Identify the runtimes and services that Bluemix offers. Explain how to get started with Bluemix. Describe Bluemix organizations, domains, spaces, and users. Create Bluemix applications. Use services in a Bluemix application. Set environmental variables that are used with Bluemix services. Deploy and run Bluemix applications. Describe how to create an IBM SDK for Node.js application that runs on Bluemix. Explain how to manage a Bluemix account with the Cloud Foundry CLI.[ ]Describe how to integrate workstation development platforms with Bluemix. Manage application code and assets with IBM Bluemix DevOps services. Work with the Git repository that is used by DevOps services. Describe the characteristics of REST APIs. Describe the use of JSON as the preferred data format for REST APIs. dentify the data services that are available on Bluemix. Describe the features in Bluemix for developing mobile applications. Create a MobileFirst Services Starter application on Bluemix. Send push notifications from Bluemix and receive them on the mobile device emulator. The workshop materials were created in August 2016. Thus, all IBM Bluemix features discussed in this Presentations Guide and Bluemix user interfaces used in the examples are current as of August 2016. Note: This IBM Redbooks publication references exercises that are NOT included with this book. The exercises are only available to students attending the course.